Building a Protomentalist Skills Scale for Infants - Melendez Jara, Carmen Magali (2019)
Protomentalist skills are the basis for developing the theory of mind, that is the cognitive component of empathy so important for the effective social bond of human beings (Riviére, 2000; Sáiz, Carbonero and Román, 2012; Westby and Robinson, 2014). The objectives of the present study were to build a scale for the evaluation of the development of Protomentalist skills  (PROTO - HM) aimed at infants under the age of 3, and to estimate its content validity. The scale was evaluated by 12 expert judges in child development in the United States of America, Chile and Peru. They observed the clarity of the statements, as well as the relevance and representativeness of the items according to the proposed theoretical model.  In order to obtain the validity of content, Aiken V was used with 95% confidence intervals. The results show that all the items, dimensions and sub-dimensions of the protomentalist skills of interaction with people and interaction with objects show values higher than .80,  these  being statistically significant with respect to the minimum criteria of Aiken (.60). At the same time it evidences a good item performance because the lower limits of the 95% confidence interval were greater than .50 in all cases.